Exploring the Effects of Lifestyle Disruptions on Physical Fitness in Children and Adolescents: a Systematic Scoping Review - Lou Dambel; Giovanna Del Sordo; Oussama Saidi; Pascale Duché (Sports Medicine - Open)
Abstract Background The objective of this scoping review was to systematically summarize the available literature investigating the impact of various lifestyle disruptions—including lockdowns, school vacations, and training cessation—on the physical fitness components of children and adolescents aged 4–18 years. Methods A search for relevant studies was conducted across PubMed and ScienceDirect databases (until May 2024). Study selection and data extraction were independently performed by two reviewers using the Cadima website. A graphical analysis was conducted to present the findings of the included studies based on the effects of each lifestyle disruption on physical fitness components, such as cardiorespiratory fitness, muscle strength, explosive strength or power, speed, agility, balance, and flexibility. Results A total of 223 records were initially identified, with 60 studies meeting the inclusion criteria for analysis. The studies assessed the impact of lockdowns (n = 8), school vacations (n = 16), and training cessation (n = 36) on various physical fitness components. The results indicated consistent declines in cardiorespiratory fitness, particularly among older adolescents, during these disruptions. In contrast, muscle strength and power remained relatively stable. Conclusion Lifestyle disruptions have a notable effect on physical fitness in children and adolescents. While different types of disruptions exert varying effects, all appear to significantly affect young populations. Further research is needed, particularly focusing on girls and incorporating better control of health-related behaviors during these periods. Understanding the long-term consequences and developing strategies to support and maintain youth fitness during such disruptions should be a priority.